What Can Student-Run Free Clinics Do for Rural Ethnic Villages in China? - Zha, Mengyi; Huang, Yunyi; Ren, Xueying; Chen, Dan (Journal of Student-Run Clinics, 2017)
The Sunshine and Love Free Clinic is China’s first and only student-run free clinic. Two successful outreach projects to a rural ethnic village, Dimen, by the volunteers of the clinic took place in 2015: a pilot project focusing on women’s health, and a larger medical service trip focusing on record building and clinical visits. While the indigenous healing is a great recourse, four major health-related issues were identified through these projects: women’s health and reproductive health; chronic illness care; a lack of formal medical training among the village clinic staff; and a lack of patient record system. This article proposes that a summer service trip model can be utilized by student-run free clinics in China to tackle these issues, and provide sustainable intermittent long term health care for the rural ethnic China in a culturally sensitive manner.